Conceptualising the erotic: metaphor in the Sumerian “Love Songs” - Carr, C (2024)

(untitled)
This thesis examines the metaphorical language of the Old Babylonian Sumerian “Love Songs”, and its role in constructing eroticism in this corpus. Using approaches borrowed from cognitive linguistics and Conceptual Metaphor Theory, I investigate how metaphor can be used as a tool for analysing the more abstract concepts and emotions essential to poems about love and sex, and how these feelings were experienced and embodied at the beginning of the 2nd millennium BCE in southern Mesopotamia. The introduction includes a literature review (1.1), as well as an overview of the compositions’ context, content, and previous interpretations (1.2). I also lay out my approach taken in analysing the metaphorical language of the “Love Songs”; this includes reading these compositions explicitly as erotic poetry, with a deliberate focus on the female expression of desire and pleasure in the corpus (1.3), as well as the methodological approach taken in analysing metaphor in Sumerian (1.4 and 1.5). The metaphorical analysis itself is broken into two sections. The first focuses on the “source domains” of the Sumerian “Love Songs”, broken into sub-sections that engage with each image in turn, and explore how this imagery maps onto its metaphorical “target domains”. Though each image is given its own sub-section, it is emphasised that these source domains consistently interact in order to construct and conceptualise the target domains that are analysed in the next chapter (3). The second section of metaphor analysis focuses on the four most prominent target domains: desire (3.1), pleasure (3.2), allure (3.3), and abundance (3.4). The concluding chapter returns to the question of context of the “Love Songs”, and the significance of writing and preserving poems that focus on intimacy and care for female pleasure (4).